2017
DOI: 10.1007/s10482-016-0815-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinct bacterial communities across a gradient of vegetation from a preserved Brazilian Cerrado

Abstract: The Cerrado biome in the Sete Cidades National Park, an Ecological Reserve in Northeastern Brazil, has conserved its native biodiversity and presents a variety of plants found in other savannas in Brazil. Despite this finding the soil microbial diversity and community structure are poorly understood. Therefore, we described soil bacterial diversity and distribution along a savanna vegetation gradient taking into account the prevailing environmental factors. The bacterial composition was retrieved by sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
4
17
0
1
Order By: Relevance
“…This is in line with patterns observed for other microbiome components, i.e. bacteria 13 , 15 , 18 , archaea 16 and fungi 17 , 18 . These patterns can be attributed to abiotic differences, such as lower fertility and soil moisture, but higher acidity and soil temperature, in the grass compared to the tree zone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in line with patterns observed for other microbiome components, i.e. bacteria 13 , 15 , 18 , archaea 16 and fungi 17 , 18 . These patterns can be attributed to abiotic differences, such as lower fertility and soil moisture, but higher acidity and soil temperature, in the grass compared to the tree zone.…”
Section: Discussionsupporting
confidence: 89%
“…Non-random co-occurrence analyses were performed using SparCC, a tool capable of estimating correlation values from compositional data 67 . For this, data tables affiliated to family level, including 18S rRNA data (protists, fungi, nematodes and animal) and 16S rRNA data (bacteria 15 and archaea 16 ), were used in the analysis. We performed the analyses on family level as previously suggested to remove artefacts from inaccurate annotation of lower taxonomic levels and the discrepancy of OTUs to sometimes consist of multiple species, while sometimes species can contain multiple OTUs 68 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The varied soil conditions found across the gradients of vegetation have influenced the bacterial diversity. 18 Interestingly, our results highlight the soil pH as a significant driver of archaea communities in these soils. According to Gorres, 29 soil pH is the main driver of archaeal community structure in soils.…”
mentioning
confidence: 63%
“…Previous studies have shown differences between bacterial diversity in the soils obtained from Cerrado in the Northeast when compared to those from the Central Plateau. 18 Therefore, we used next-generation sequencing of the 16S rRNA gene in soil samples from vegetation gradients obtained from Campo graminoide, Cerrado stricto sensu, Cerradao and Floresta decidual to understand the diversity of Archaea in the soils of Cerrado in Northeastern Brazil.…”
mentioning
confidence: 99%